Physoschistura harkishorei, a new species of loach from Arunachal Pradesh, north-eastern India (Teleostei: Nemacheilidae) - Das, Debangshu Narayan; Darshan, Achom (Zootaxa, 2017)
Physoschistura harkishorei, a new species of nemacheilid loach, is described from the Dibang and Lohit Rivers of Arunachal Pradesh, north-eastern India. The new species can be distinguished from all known congeners by the combination of the following characters: the second branched ray of pectoral fin with a distal filamentous extension; body colour pattern consisting of 9–10 vertically-elongated brownish spots or blotches along the flank, and 8–10 brownish saddles on back, the saddles not contiguous with the lateral blotches; lateral line complete; prominent, well-developed pelvic-fin lobe; a well-developed free posterior chamber of the air-bladder; and caudal fin with 7+8 branched rays. The new species occurs sympatrically with Physoschistura dikrongensis and P. elongata in the Brahmaputra basin.